A Randomized Placebo Controlled Clinical Trial to Determine the Impact of Digestion Resistant Starch MSPrebiotic® on Glucose, Insulin, and Insulin Resistance in Elderly and Mid-Age Adults - Alfa, Michelle J.; Strang, David; Tappia, Paramjit S.; Olson, Nancy; DeGagne, Pat; Bray, David; Murray, Brenda-Lee; Hiebert, Brett (Frontiers in Medicine, 2018)
Introduction: Type 2 Diabetes (T2D) has reached epidemic proportions in North America. Recent evidence suggests that prebiotics can modulate the gut microbiome, which then plays an important role in regulating lipid metabolism, blood glucose, and insulin sensitivity. As such, prebiotics are appealing potential therapeutic strategies for pre-diabetes and T2D. The key objectives of this study were to determine the tolerability as well as the glucose and insulin modulating ability of MSPrebiotic® digestion resistant starch in healthy middle aged and elderly adults. Materials and Methods: This was a prospective, blinded, placebo controlled study. Pre-diabetes and diabetes were among the exclusion factors. Elderly (>70 years) and mid-age (30 to 50 years) Canadian adults were recruited and, after 2 weeks of consuming placebo, they were randomized to consume 30 grams of either MSPrebiotic® or placebo per day for 12 weeks. In total, 42 elderly and 42 mid-age participants completed the study. Blood samples were collected over the 14 week study and analyzed for glucose, lipid profile, and CRP, lipid particles, TNF-α, IL-10, insulin and insulin resistance. Results: At baseline, the elderly population had a significantly higher percentage (p <0.01) with elevated glucose and significantly higher TNF-α (p < 0.01) compared to mid-age adults. MSPrebiotic® digestion resistant starch was well tolerated in both mid-age and elderly adults. There was a significant difference over time in blood glucose (p = 0.0301) and insulin levels (p = 0.009), as well as insulin resistance (HOMA-IR; p = 0.009) in elderly adults who consumed MSPrebiotic® compared to placebo. No significant changes were found in mid-age adults. Conclusions: Our results suggest that dietary supplementation with prebiotics such as MSPrebiotic® may be part of an effective strategy to reduce insulin resistance, a major risk factor for developing T2D, in the elderly.